Sources of health information among U.S. cancer survivors: results from the health information national trends survey (HINTS) - Inimfon Jackson; Ikponmwosa Osaghae; Nnenna Ananaba; Aniekeme Etuk; Nsikak Jackson; Onyema G Chido-Amajuoyi (AIMS Press, 2020)
Background: Health information is crucial for preservation of health and maintenance of healthy practices among cancer survivors. This study examines the sources and factors associated with choice of health information source among cancer survivors and those without a cancer history. Methods: We examined health information sources utilized by cancer history between 2011-2014 and 2017-2018 using the Health Information National Trends Survey (HINTS). Factors associated with seeking health information were examined using multinomial logistic regression. Data from HINTS 4, cycles 1-4 (2011-2014) and HINTS 5, cycles 1-2 (2017-2018) were combined and used for all analyses. HINTS-FDA, cycles 1-2 (2015-2017) were excluded from this study because the question about a cancer history was not asked. Results: Over half of cancer survivors (52.7%) and those without a cancer history (60.9%) obtained their health information through the media. Among cancer survivors, factors associated with health information seeking either through the media or interpersonal communication relative to not seeking information were age, gender, level of education, income, marital status and having a regular healthcare provider. Male survivors were 39% less likely to seek health information from the media (aOR: 0.61; 95% CI: 0.38-0.99) while those with a regular health provider had significantly higher odds of seeking health information via interpersonal communication (aOR: 1.92; 95% CI: 1.09-3.38). In addition, widowed cancer survivors had lower odds of seeking health information from either interpersonal communication (aOR: 0.28; 95% CI: 0.13-0.60) or the media (aOR: 0.30; 95% CI: 0.13-0.69). In the study population without a cancer history, compared to non-Hispanic whites, non-Hispanic blacks, Hispanics and non-Hispanic other categories were significantly less likely to seek health information from the media rather than not seek health information. Conclusion: Socioeconomic status, marital status, gender and age are important correlates of choice of health information source among cancer survivors in the US. These factors may be useful in guiding interventions aimed at various groups of cancer surviving populations to ensure that they improve their health seeking behaviors.